Nossa Santa Maria: um programa de educação para a participação (WEB)cidadã impulsionado pelas tecnologias educacionais em rede - Koltermann, Andrewes Pozeczek (2016)
The present study, developed during Professional Masters in Network Educational Technologies of the UFSM, is based on the Nossa Santa Maria Program, focused on education for the citizen participation in a private college. It is framed in the research line Management of Network Educational Technologies, within the Area of Concentration Educational Technologies in Network for Innovation and Democratization of Education. The overall aim was to understand the limits and potential of Network Educational Technologies (NET) in the teaching-learning process to increase citizen participation in the Nossa Santa Maria Program. The theoretical foundations of this work are based on Social Sciences authors, specifically those from the NET field. Methodologically, it adopted the investigation dynamics typical of Case Studies, based on application of interviews and participant observation. The practical contribution has been the implementation of a TeachingLearning Virtual Environment (TLVE), resulting in incremental innovation in the educational sphere at the Nossa Santa Maria Program. The actions and diagnoses from the Case Study originated, as an outcome of the master's programme, the preparation of a Manual of Best Practices. The aim for the future is to enable a fully online version of Nossa Santa Maria Program, based on TLVE, already implemented, and on the guidelines specified in the Manual of Best Practices. Conclusively, it should be highlighted that the network society's context drives the recognition/knowledge of web citizenship based on methodologies of academic work sustained by three pillars: education, research and extension, with structure, tools and instruments mediated by the NET.